The use of non-pharmacological adjuvant therapies for cancer pain: a narrative review in the context of dance (Research, Society and Development, 2022)
Cancer is one of the leading causes of morbidity in the globe, with more than half of patients reporting pain as a result of the disease. By reducing cancer-related pain, dance has the potential to redefine the life of patients independently of their cure prognosis. This review investigated the benefits of dance as adjuvant, non-pharmacological therapy for cancer treatment. To identify studies related to this topic, we searched the Cochrane Library, PUBMED, Scielo, BVS, Embase, CINAHL, and PsycINFO databases. However, we found few published systematic reports investigating the effects of dance in cancer treatment. The numbers are even smaller when we considered the relationship between dance and cancer pain. Although there is a small number of publications on this theme, we reviewed studies that indicate that there is a positive relationship between dance practice and cancer pain management. Moreover, we found that the decline of pain contributed to the better life quality of patients with cancer. We concluded that dance is a physical practice that may improve patients’ quality of life. Regarding the estimations of cancer diagnosis and pain during disease development and therapy, it is fundamental new studies and clinical trials that integrate dance as adjuvant therapy for improving cancer pain and patient’s life quality.